2022
DOI: 10.7717/peerj.12770
|View full text |Cite
|
Sign up to set email alerts
|

Tentacle patterning during Exaiptasia diaphana pedal lacerate development differs between symbiotic and aposymbiotic animals

Abstract: Exaiptasia diaphana, a tropical sea anemone known as Aiptasia, is a tractable model system for studying the cellular, physiological, and ecological characteristics of cnidarian-dinoflagellate symbiosis. Aiptasia is widely used as a proxy for coral-algal symbiosis, since both Aiptasia and corals form a symbiosis with members of the family Symbiodiniaceae. Laboratory strains of Aiptasia can be maintained in both the symbiotic (Sym) and aposymbiotic (Apo, without algae) states. Apo Aiptasia allow for the study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…C3). This result was consistent with the development period (Presnell, Wirsching & Weis, 2022). Furthermore, at a concentration of 10% PVC leachate, the regeneration of E. diaphana was severely compromised.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…C3). This result was consistent with the development period (Presnell, Wirsching & Weis, 2022). Furthermore, at a concentration of 10% PVC leachate, the regeneration of E. diaphana was severely compromised.…”
Section: Resultssupporting
confidence: 91%
“…Exaiptasia diaphana exhibits asexual reproduction capability, growing from pedal lacerations, a small portion of tissue deriving from the margin of the pedal disk and the body column. This produces of crescent-shaped fragments that successfully regenerate into fully formed polyps within a few weeks (Clayton & Lasker, 1985; Presnell, Wirsching & Weis, 2022) (Figure 3. C1).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to this study, there have been other attempts at utilizing the sea anemone Exaiptasia in understanding the regeneration processes (e.g. Singer, 1971 ; van der Burg et al, 2020 ; Presnell et al, 2022 ). Nevertheless, how miRNAs contribute to cnidarian regeneration is relatively understudied in cnidarians ( Krishna et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Samuel A. Bedgood (Postdoc, Weis lab, Oregon State University) addressed the role of the crosstalk between endosymbionts and their hosts during development. Previous work demonstrated that Aiptasia containing symbionts developed faster than their aposymbiotic (i.e., without symbionts) counterparts [ 34 ]. Bedgood used symbionts which do not provide the necessary nutrition to their hosts (i.e., heterotrophic) to show that symbiont-host communication and not nutrition mediates the effects on developmental rates.…”
Section: The Physiological Response Of Cnidarians To Environmental Ch...mentioning
confidence: 99%